Solid polymer electrolytes with hydrates for structural supercapacitors. (July 2022) - Joyal, Nathaniel; Chang, Yu-Che; Shonar, Mohammed; Chalivendra, Vijaya; Shen, Caiwei
Abstract: Structural supercapacitors that simultaneously carry mechanical loads and store electrical energy show great promise to increase the functionality and efficiency of countless mobile systems. Current iterations of all structural supercapacitors use bi-continuous electrolytes with two phases that provide mechanical and electrochemical functions separately. Here we demonstrate a single-phase hydrate-based solid polymer electrolyte with improved multifunctionality. The new structural electrolyte composed of polyethylene terephthalate (PET) and lithium perchlorate trihydrate (LiClO4 ·3H2 O) is created through mix-melting of PET and LiClO4 followed by controlled hydration of the salt. The bound water molecules in the hydrates significantly improve the ionic conductivity while retaining the high mechanical stiffness of the electrolyte, which reduces the trade-off between the two functions as in previous reports. The electrolyte with the optimal composition achieves a flexural modulus of 2.1 GPa with an ionic conductivity of 1.05 μS/cm. Moreover, the single-phase electrolyte exhibits a much better electrochemical interface with electrodes compared to other structural electrolytes. The interfacial capacitance measured with our electrolyte is the same order of magnitude as that tested with a liquid electrolyte. The creation of this electrolyte allows for the development of more efficient structural supercapacitors. The strategy of introducing bound solvent molecules to improve the ionic conductivity without sacrificing the mechanical properties of solid polymer electrolytes can also be used to develop better electrolytes for all-solid-state batteries. Graphical abstract: Unlabelled Image Highlights: Solid polymer electrolytes are prepared using base polymers and hydrates. Controlled amount of water retains the solid phase of the electrolyte. Such electrolytes show high mechanical stiffness and good ionic conductivity. Such electrolytes have excellent electrochemical interface with electrodes. The overall multifunctionality is improved compared to previous electrolyte designs.